USE OF PROJECT METHOD BASED ON DIGITAL LITERATION IN WRITING LEARNING OBSERVATION REPORT (International Conference on Elementary Education, 2018)
This research is motivated by the findings of problems that occur in class V MI Nurul Huda Rancaekek, Bandung Regency, when the Indonesian learning process in aspects of writing skills takes place the learning activities of students are very lacking. This is due to the inability of students to write reports with the appropriate observation report stages, because there is no guidance and modeling how to write observation reports conducted by the teacher. Then, students are unable to write reports by paying attention to the correct spelling, because the teacher does not provide opportunities for students to collaborate and discuss. To overcome these problems, learning innovations are carried out that are able to engage students actively, namely by applying digital literacy-based project methods. The project method is a way of presenting a lesson with a starting point from one problem, then discussing it from various related aspects so that the solution is overall and meaningful. Digital literacy is the interest, attitude and ability of individuals who use digital technology and communication tools to access, manage, integrate, analyze and evaluate information, build new knowledge, communicate with others in order to participate effectively in society. This study aims to obtain knowledge about learning to write observation reports before studyingwrite report. By using the project method, students can gain learning experience in sharing activities and responsibilities so that students' activities and abilities in writing observation reports increase. The method used in this study is a classroom action research method. Classroom Action Research (CAR) is a research conducted in class in the form of learning practices with the aim of improving and improving student learning by taking steps, namely: planning, action, observation and reflection. The data collection technique uses observation report observation sheets and test questions.